Human capital, financial constraints, and innovation investment persistence. Issue 3 (1st September 2020) - Peng, Hongxing; Tan, Hongping; Zhang, Yin
ABSTRACT: We examine the impact of human capital on innovation investment persistence using a sample of high-tech companies listed in the Chinese A-share market for the period 2009–2017. We find that human capital mitigates the negative effect of financial constraints on innovation investment persistence. We further explore the mechanism through which human capital at the management and employee levels affects innovation investment persistence. We find that management human capital affects innovation investment persistence through the expectation of authorised patents, while employee human capital affects the persistence through salary stickiness. Furthermore, we find that management human capital contributes to an increase in future granted patents through persistent innovation investment.